مضامني الرتبية العقدية يف القرآن والسنة [The Significance of Theological Education in the Quran and Sunnah] - Mohd Hasrul, Shuhari; Dahan Ali, Mohammed Alqabatli; Omar Ahmed, Ahmed Moqbel Mareai (2019)
The Quranic methods are characterized with educational content, values, principles and great and lofty goals. However, when Muslims left this great legacy they deviated from the mainstream. The research problem shows the spread of some intellectual and doctrinal deviations among the Muslim societies today, and this have made them see the non-Islamic approach as a better alternative to theirs. This indicates their lack of proper understanding of the Qur'an and Sunnah contents; they do not have proper training on the Qur'an and do not comprehend the rites of Allah SWT upon them. Another extreme religious understanding is the fatwa legalizing bloodshed and violation of privacy.. The purpose of this paper is to indicate the ideological and intellectual deviations of the Muslim societies, and to illustrate the danger of the intellectual and secular imbalance (extremism) and its impact on the contemporary Muslim society. The paper uses inductive and descriptive approach to extract these contents and check the position of the Muslim community through the contents. The research concludes that the Muslim societies suffer serious deviations. And upon serious findings and contemplations, we see that there are suspicious organizations supporting them both materially and morally. And there is another extreme sect legalizing the infamous bloodshed. Islam is a religion of moderation, maintainin moderation between extremism and negligence. It is a safe path to practicing the book of Allah and the Sunnah of his Prophet (SAW).